The Epistemology of Justice. Issue 1 (5th March 2020) - Anderson, Elizabeth
Abstract: In arguing about justice, different sides often accept common moral principles, but reach different conclusions about justice because they disagree about facts. I argue that motivated reasoning, epistemic injustice, and ideologies of injustice support unjust institutions by entrenching distorted representations of the world. Working from a naturalistic conception of justice as a kind of social contract, I suggest some strategies for discovering what justice demands by counteracting these biases. Moral sentiments offer vital resources to this end.